PENETAPAN KADAR BESI (Fe) PADA BAYAM HIJAU, BAYAM RAJA DAN BAYAM DURI DI PASAR MOJOSONGO - Widiastuti Widiastuti; Fitria Aini (Caraka Tani: Journal of Sustainable Agriculture, 2008)
Vegetables are essential for the body and easy to be found everywhere. Amaranth is highly nutritious vegetale and most people enjoy it. Amaranth is the source of vitamin A, C and aslo Fe, Ca and K as much as 40%. The Fe content in amaranth is high enough, twice more than other vegetables. Lack of iron in the body will lead to iron deficiency anemia disease.The method used analyzing iron in green amaranth, king amaranth and thorny amaranth is UV-visible Spectophotometer. The principal of UV-visible spectophotometers is visible beam adsorption by a color solution. Determinant of iron in the three kinds of the samples used KCNS 20% solution. Positive reaction indicated by blood-red color. The iron (Fe) contents in green amaranth was 5,11 mg/100 g; king amaranth’s was 5,615 mg/g and thorny amaranth’s was 4,88 mg/g. The result indicated the king amaranth had highest iron content.